The efficacy of strategies used to minimise and prevent cisplatin ototoxicity in patients - Chakara, Zenzo Stanford (Division of Comm. Sciences and Disorders, 2019)
This study aimed to evaluate the efficacy of different treatment modifications used to prevent or minimise hearing loss during Cisplatin-based chemotherapy as part of patient management at Groote Schuur Hospital. The study also sought to compare different ototoxicity grading criteria; namely the National Cancer Institute Common Terminology Criteria for Adverse Events Version 4 (CTCAE v4) and TUNE criteria, with respect to early identification of changes in the patient’s hearing thresholds following treatment with ototoxic drugs as well as ability to guide recommendations for aural rehabilitation including hearing amplification. Background Non-communicable diseases (NCD) (including cancer, diabetes, cardiovascular and chronic respiratory diseases) are responsible for an estimated 36 million deaths annually across the world. Approximately 80 % of these deaths occur in developing countries. Cancer, the NCD of interest in this study, causes an estimated 8.2 million deaths per year, globally and about 70 % of these occur in developing countries. In South Africa, cancer is estimated to cause approximately 40 000 deaths per annum, which is more than the number of deaths caused by a combination of HIV/AIDS, TB and malaria every year. Cisplatin is the most common and effective anti-cancer drug for most types of cancers. However, it is also associated with severe adverse effects, including hearing loss. Cisplatin-induced hearing loss is usually bilateral, highfrequency sensorineural hearing loss and is permanent. Cisplatin-induced hearing loss can lead to communication difficulties, lack of participation, loss of employment and social isolation. This decreases patients’ quality of life. Prevention of ototoxicity relies on serial audiologic monitoring to detect any significant change in patients’ hearing thresholds that may be resulting from chemotherapy treatment. When a deterioration in the patient’s hearing thresholds is detected, treating physician(s) can decide on whether to modify the patient’s treatment to prevent further deterioration of hearing or not. Some of the common treatment modifications used by physicians include; reducing the drug dose administered to the patient, changing from Cisplatin to a less ototoxic drug such as Carboplatin or keeping a patient on Cisplatin only regimen (no treatment modification). However, there is 8 currently lack of research evidence that document the effectiveness of these treatment modifications with respect to preservation of the patient’s hearing thresholds. Also, given that there are several ototoxicity grading scales available that can be used to grade severity of ototoxicity-induced hearing loss, there is currently a lack of uniformity regarding communication of the severity of hearing loss across different professionals. There is a need to identify or develop an ototoxicity grading criterion which can be adopted by different professionals to communicate results during ototoxicity monitoring of patients. Research design This study employed a descriptive, quantitative retrospective cohort design. Medical folders of patients who underwent cisplatin chemotherapy treatment and had their hearing thresholds monitored at Groote Schuur Hospital during from 2011 up to 2016 were reviewed. Methods A non-probability, convenience sampling method was used to select medical folders that underwent review. Data which were extracted from the patients’ medical folders includes demographic information (for example age and sex,), chemotherapy treatment information including type and dose of treatment; and audiological information including baseline, checkup and exit audiogram thresholds. Data obtained from the folders were analysed using R, a software environment for statistical computing and graphics. Descriptive statistics and the following inferential statistical tests, Chi-squared, Fisher’s exact tests and the Wilcoxon signed-rank test for paired samples, were used to determine significant associations between hearing loss and several factors revealed in the data. The American Speech-Language and Hearing (ASHA, 1994) criteria were used to determined incidence of significant threshold shift whilst the CTCAE v4 was used to determine both incidence of hearing loss and severity of the loss. The CTCAE v4 and TUNE criteria were compared based on incidence of hearing and ability to predict need for hearing amplification Results A total of 128 medical folders met inclusion criteria for this study and the following were the patient characteristics; median age = 43 years (range: 18 – 75 years); 92 males, 36 females; average length on treatment: 13.45 weeks). Out of these, 64 had information on the type and dose information of chemotherapy drug used during the period when monitoring of ototoxicity was conducted. The American Speech-Language and Hearing (ASHA) criteria revealed 9 ototoxicity in 74.2 % (95/128) of the sample. The Wilcoxon signed-rank test for paired samples showed a significant difference (p = 0.0000000039, p < 0.05) between follow-up and exit monitoring thresholds which indicated a significant decline of patients’ hearing thresholds throughout the treatment duration. There were no statistically significant associations between age, duration of treatment and treatment modification. The study showed three treatment modifications which included dose adjustment (reduction), switching drug and continuing with the same drug. There was no significant association between treatment modifications and hearing loss. The CTCAEv4 criteria identified more people (53.9 %) who experienced a deterioration in their hearing thresholds than TUNE criteria (41.7%). However, TUNE performed better with respect to identifying patients who are likely to be candidates for further audiological rehabilitation including hearing amplification. Conclusion This study found a high incidence of cisplatin-induced hearing loss despite the possible modification of treatment. This shows that current strategies that are used by physicians at GSH Radiation Oncology department to prevent or minimize further deterioration of the patient’s hearing thresholds during cisplatin chemotherapy can arguably be rendered ineffective. This is owing to the inability of conventional audiometry to detect hearing loss before it affects the speech frequencies. There was no significant association between hearing loss and age, dose, duration of treatment and treatment modification. The study also showed that CTCAE v4 grading criteria detected a higher incidence of ototoxicity than the TUNE criteria. However, the TUNE criteria were better at detecting the number of patients who need further audiological rehabilitation than the CTCAE v4. Therefore, both scales have their strengths and weaknesses. Implications of the study include the incorporation of Extended High Frequency Audiometry (EHF) and Distortion Product Otoacoustic Emission (DPOAE) testing into the monitoring protocol where possible to allow for early detection and intervention of ototoxicity. Incorporation of otoprotectors into the prevention protocol is suggested as they have recently shown otoprotective efficacy in animal models without interrupting Cisplatin’s therapeutic agency. Finally, more studies are required to validate the TUNE grading criteria to explore its utility as an ototoxicity grading criterion that can be universally used to communicate ototoxicity outcomes during Cisplatin chemotherapy.